2013
DOI: 10.2207/qjjws.31.168s
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ^|^sigma; Phase Precipitation in Type 316FR Stainless Steel Weld Metal

Abstract: Through the isothermal ageing treatments at 873, 923, 973, and 1023K, precipitation of sigma (σ) phase in type 316FR stainless steel weld metal was examined based on the kinetics approach. Microstructural examination was performed by scanning electron microscopy (SEM), electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). The dominantly precipitated phases were sigma (σ) and chi (χ), nucleated at δ-ferrite/austenite (γ) interface or interior of the δ-ferrite grains, consuming the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It was also reported that, for a type 316FR austenitic stainless steel weld metal under isothermal ageing treatments, σ-phase usually precipitates around grain inclusions, incoherent grain boundaries and δ-Fe/ γ-Fe grain boundaries region [35]. The solution treatment temperature of 800 °C (Figure 4b) led to an increased grain-size of σ (CrFe) phase and to a higher fraction of σ (Cr-Fe) phase, with an average grain-size close to 8-9 μm.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…It was also reported that, for a type 316FR austenitic stainless steel weld metal under isothermal ageing treatments, σ-phase usually precipitates around grain inclusions, incoherent grain boundaries and δ-Fe/ γ-Fe grain boundaries region [35]. The solution treatment temperature of 800 °C (Figure 4b) led to an increased grain-size of σ (CrFe) phase and to a higher fraction of σ (Cr-Fe) phase, with an average grain-size close to 8-9 μm.…”
Section: Resultsmentioning
confidence: 93%
“…For instance, in the case of a stabilized AISI 347 austenitic stainless steel under heat treatments, it was shown that σ (Cr-Fe) phase precipitation is a very slow process and usually small grains and very low proportions are obtained during slow cooling [34]. It was also reported that, for a type 316FR austenitic stainless steel weld metal under isothermal ageing treatments, σ-phase usually precipitates around grain inclusions, incoherent grain boundaries and δ-Fe/ γ-Fe grain boundaries region [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Austenite is the equilibrium phase at high temperature; 6 delta-ferrite (d), intermetallic compounds sigma (s), and carbides are not equilibrium phases that can redissolve by appropriate solution treatments. 13 The high-temperature heat treatment at 1100 C with enough holding time (3 h) promotes the dissolution of hard and brittle intermetallic sigma (s) phase, 8,9 leaving mainly two phases (g and d) in the microstructure of WAAM SS316.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that the σ and τ phases are formed due to Cr diffusion towards the grain boundaries during slow cooling after forging [19,20]. It was also shown that σ phase precipitation is a very slow process and small grain sizes and low contents of σ phase are found in the material after soft cooling [21,22], σ phase precipitating mainly in the ferrite-austenite grain boundaries area and around inclusions or incoherent grain boundaries [19,23]. Regardless of the deformation mode, the temperature can improve the hot formability of the steel.…”
Section: Introductionmentioning
confidence: 99%